(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Human resource Practices is a new way of considering how individuals should be treated as employees in the workplace. (HRM)Managing a company’s most precious asset through human resource management requires a well-thought-out strategy; the employees who, both individually and collectively, help the firm accomplish its objectives. Human resources are seen as being particularly crucial to long-term organizational performance, according to the philosophy of human resource management. Recruitment and selection plays a vital role in the process of HRM.